Answer:
1/12
Step-by-step explanation:
Total sub consumed = ¼ + ⅔
= [3(1) + 4(2)]/12 (LCM is 12)
= 11/12
Left = 1 - 11/12 = 1/12
<span>Because the four numbers are consecutive, we can call the first one x, and the other three are x+1, x+2, and x+3, respectively.
x * (x+1) = (x+2) * (x+3) - 38
x^2 + x = x^2 + 5x +6-38
x^2 + x = x^2 + 5x - 32
-4x = -32
x=8
The four numbers are 8, 9, 10, and 11
check solution: 8*9=10*11-38
72=110-38
72=72</span>
Answer: ![\frac{11tc+5g}{66t}=n](https://tex.z-dn.net/?f=%5Cfrac%7B11tc%2B5g%7D%7B66t%7D%3Dn)
Step-by-step explanation:
You have the equation
.
Then, to solve for the variable
from the equation you need:
Make the subtraction of the right side of the equation:
(As the denominators are 1 and
, the least common denominator is
)
![c=\frac{(6n)(11t)-5g}{11t}\\\\c=\frac{66nt-5g}{11t}](https://tex.z-dn.net/?f=c%3D%5Cfrac%7B%286n%29%2811t%29-5g%7D%7B11t%7D%5C%5C%5C%5Cc%3D%5Cfrac%7B66nt-5g%7D%7B11t%7D)
Multiply
to both sides:
![(11t)c=(\frac{66nt-5g}{11t})(11t)\\\\11tc=66nt-5g](https://tex.z-dn.net/?f=%2811t%29c%3D%28%5Cfrac%7B66nt-5g%7D%7B11t%7D%29%2811t%29%5C%5C%5C%5C11tc%3D66nt-5g)
Add
to both sides:
![11tc+5g=66nt-5g+5g\\\\11tc+5g=66nt](https://tex.z-dn.net/?f=11tc%2B5g%3D66nt-5g%2B5g%5C%5C%5C%5C11tc%2B5g%3D66nt)
And finally divide both sides by
:
![\frac{11tc+5g}{66t}=\frac{66nt}{66t}\\\\\frac{11tc+5g}{66t}=n](https://tex.z-dn.net/?f=%5Cfrac%7B11tc%2B5g%7D%7B66t%7D%3D%5Cfrac%7B66nt%7D%7B66t%7D%5C%5C%5C%5C%5Cfrac%7B11tc%2B5g%7D%7B66t%7D%3Dn)
D dddddddddddddddddddddfdfddxdddd